Experimental investigation on membrane fouling mitigation by solid-liquid fluidization - Wang, Jingwei (2018)
Particle fluidization is a promising unsteady-state shear means of mitigating membrane fouling. It has the potential to lower energy requirement and prolong membrane lifespan in membrane-based wastewater treatment processes. In particular, the particles facilitate back-transport in the polarization layer and also play the role of mechanical scouring agents, the latter of which is dominant for millimeter-sized particles. In this study, an accelerometer was first successfully used to unveil the dynamics of GAC particles with three particle diameters (namely, 1.20 mm, 1.85 mm, and 2.18 mm). The energy contained in the accelerometer signal representing the solid phase was consistent with the extent of fouling mitigation in the filtration tests. The smallest GAC particle with a particle diameter of 1.20 mm conferred the least scouring efficiency, while both the larger particles with diameters of 1.85 mm and 2.18 mm provided similar scouring efficiency. The impact of particle diameter is due to the balance between particle inertia, and the difference between superficial liquid velocity and minimum fluidization velocity. Furthermore, in a practical pilot-scale AnFMBR with wastewater, the accelerometer was shown to be able to diagnose the de-fluidization of the GAC particles due to severe clogging issues, which thereby eliminated the fouling mitigation capacity. Trends in the trans-membrane pressure (TMP) and flux data did not indicate de-fluidization of the GAC particles. In order to further improve this technique in terms of scouring efficiency and energy requirement, the hydrodynamics of the fluidized GAC particles, and correspondingly the relationship between the particle behavioural characteristics and the extent of membrane-fouling mitigation were investigated. Directly correlating particle behavior with membrane fouling trends showed that higher particle velocities, particle concentration and particle momentum generally all showed a negative correlation with dTMP/dt. Of the three characteristics (namely, particle velocity, concentration and momentum), the negative correlation between dTMP/dt and particle momentum was most pronounced, which suggests that momentum transfer between the GAC particles and the membrane represents a key mechanism effecting the scouring to diminish membrane fouling. More in-depth studies of the improvement of micrometer-sized particulate (namely, polystyrene foulant) critical flux in the presence of fluidized GAC particles was studied, whereby a Direct Observation Through the Membrane (DOTM) technique was used to measure the membrane critical flux locally and overall. It was found that (i) the fluidized GAC particles increased critical flux by an order-of-magnitude relative to that with tangential liquid shear alone; (ii) the overall critical flux increased with the increase of GAC particle diameter or power input; and (iii) a higher power input was required for sufficient bed expansion to enable more consistent critical flux values over the whole membrane height. Accordingly, the impact of different overall GAC concentrations, which give different expanded bed heights, on the extent of fouling mitigation was investigated in this study. The results indicate that the highest overall concentration was advantageous in terms of enabling (i) higher membrane fouling mitigation at a lower power required per unit permeate (Pp) for the polystyrene foulant but not bentonite foulant; and (ii) more similar local critical flux values over the three heights along the membrane investigated, which implies more uniform fouling mitigation across the membrane. The relative benefits of adjusting overall GAC concentration versus the particle diameter of the GAC media were also critically assessed. Finally, the effect of the sphericity (φ) of the fluidized media on the extent of fouling mitigation was studied. Three types of millimeter-sized rice media were used as the fluidized media. Relative to GAC media, the rice media had similar particle densities and similar particle diameters, but offered much lower sphericities (lowest sphericity in this study was 0.54) due to the greater aspect ratios. The results indicate that the correlation between sphericity of the fluidized media and hydrodynamics (and the attendant fouling mitigation) was not straightforward, likely tied to the influence of drag on the countering effects of media-membrane contact and particle rotation. In conclusion, this thesis gave a deep understanding of the fluidized GAC particle behavioral characteristics and the correlation with the extent of membrane-fouling mitigation in solid-liquid fluidization membrane filtration systems. The parameters investigated included GAC particle diameter (dp),overall GAC concentration, fluidized particle sphericity (φ), superficial liquid velocity (Ul) thereby the power requirement (Pr), and height along the vertically aligned membrane. The findings are expected to be valuable in the optimization of membrane fouling mitigation towards more energy-efficient in a solid-liquid fluidization membrane filtration system.